ABOUT THE WORK RADD-L-MUKHTAR AND ITS SOURCES - Tursunov Muxiddin Dovudovich (Modern American Journals, 2025)
The introduction to an analysis of Radd-l-Mukhtar is vital in situating the work within the broader context of Islamic jurisprudence and its socio-political implications. It serves as a gateway to understanding how this text not only embodies legal doctrine but also reflects the cultural and historical circumstances of its time. As noted in research surrounding Ahmad Sanusis works, which utilized interpretation as a means to address colonial policies, Radd-l-Mukhtar similarly conveys a critical perspective on law as it interacts with societal needs and governance (Lutfi L, p. 53-72). Furthermore, exploring local wisdom, as seen in the religious practices of communities like Kaloran, illustrates how cultural nuances shape interpretations of religious texts and foster tolerance (Sodiqin A et al., p. 159-180). Therefore, this introduction establishes the foundation for a deeper exploration of Radd-l-Mukhtar and its multifaceted sources, inviting readers to consider the interplay between law, culture, and politics.
Keywords: Radd-l-Mukhtar; socio-political; religious texts